Lire l’organisation scripto-iconique des sites politiques - Rania Adel (Communication)
The Internet offers a vast field of research for linguists in general and semioticians in particular. The author studied the construction methods of the home page of the two main French political parties: the Union pour un mouvement populaire (UMP) and the Parti socialiste (PS). Her aim is to extract the governing rules, the semiolinguistic criteria to which they obey and what their main components are.